Ameliorative Effect of Chronic Moderate Exercise in Smoke Exposed or Nicotine Applied Rats From Acute Stress - YARAT, AYŞEN; AKAKIN, DİLEK; KASIMAY ÇAKIR, ÖZGÜR; KAYA, ÖZLEM TUĞÇE (OXFORD UNIV PRESS, 2015)
Introduction: Physical activity has been found to be related with many health benefits. Our aim was to investigate the effect of chronic moderate exercise from acute stress on nicotine and cigarette smoke exposed rats. Methods: Male Sprague Dawley rats (200-250 g, n = 48) were divided into 6 groups as non-exercised, exercised, smoke exposed, smoke exposed and exercised, nicotine applied, and nicotine applied and exercised. Nicotine bitartarate was applied intraperitoneally (0.1 mg/kg/day) for 5 weeks, and cigarette smoke was exposed in a ventilated chamber. After 1 week of nicotine application or smoke exposure, moderate exercise training protocol was applied to exercise groups. At the end of the experiments, acute stress induction was made to all groups by electric foot shock. Holeboard tests were performed before and after the experiments. Biochemical and histological analyses were performed in lung, liver, colon, stomach, and gastrocnemius tissues. Results: Malondialdehyde levels were increased in all tissues of smoke exposed group (p < .05-.01) except gastrocnemius tissue compared to non-exercised group and were decreased with exercise (p < .05-.001). Myeloperoxidase levels were increased in lung, liver and colon tissues of smoke exposed group (p < .05-.001) and liver and colon tissues of nicotine applied rats (p < .01-.001) and decrease with exercise in liver and colon tissues of both smoke exposed or nicotine applied groups (p < .05-.01). In all tissue samples, increased histological injury scores (p < .05-.001) decreased significantly with exercise (p < .01-.001). Conclusion: Biochemical parameters and histological scoring indicated increased tissue injury due to nicotine application and cigarette smoke exposure and exercise training ameliorated these effects in most of the tissues of acute stress induced rats.
Keywords: TOBACCO; BEIRUT